NANDA-I NURSING DIAGNOSES BASED ON WANDA HORTA'S THEORY - Isabela Ubaldo; Eliane Matos; Nádia Chiodelli Salum (Universidade Federal do Paraná, 2015)
The present study aimed to investigate nursing problems usually identified in the nursing records of patients admitted to medical units, relating them to the North American Nursing Diagnosis Association-International (NANDA-I) diagnostic classification. It is a quantitative descriptive study. Documental analysis was used for data collection. Data was collected in August 2011, from the records of 134 patients, and 141 nursing problems were detected, and 35 different diagnoses were identified. Most of them concern diagnoses related to psychobiological (117) and psychosocial (24) needs. No diagnoses related to psychospiritual needs were identified. It is concluded that nurses prioritize the physical problems of the patients at the expense of social and spiritual problems.